A brainstem mass of Müllerian type Epithelial Origin without any primary cancer source. (January 2019) - Fiani, Brian; Quadri, Syed A.; Farooqui, Mudassir; D'Apuzzo, Massimo; Rosser, Robert J.; Berman, Blake W.; Noel, Jerry; Xin, Xin S.; Badie, Behnam; Ramachandran, Anirudh; Siddiqi, Javed
Highlights: Very rare case of a calcified heterogeneously contrast enhancing brainstem mass of Müllerian origin in a patient with no female genital tract cancer; and with ventriculoperitoneal (VP) shunt placement for congenital hydrocephalus. This is the very first case to report a Müllerian mass in the brain stem. This only the second case that supports the notion for retrograde travel of tumor cells against the CSF flow. We highlight the importance of diagnostic assessment of VP shunts after their surgical removal for pathologic evaluation, especially in patients with both neural and extraneural tumors. This case also highlights the use of catheters with filters and the use of intraperitoneal chemotherapy in cases of extraneural abdominal high-grade malignancies with or without the presence of peritoneal infiltration in order to avoid dissemination through VP shunts. Abstract: Brainstem tumors are rare, even rarer is a brainstem tumor containing tissues of an embryologic gynecologic origin. We report a very rare case of presence of a calcified heterogeneously contrast enhancing brainstem mass of Müllerian origin in a patient in a 38 year old female with no female genital tract cancer and past surgical history of ventriculoperitoneal (VP) shunt placement for congenital hydrocephalus. To our knowledge this is the very first and unusual case of a mass of gynecologic origin in the brainstem region especially in the setting of no history of gynecological tumor. The authors also reviewed the literature for all tumors reported for anterograde and retrograde dissemination of tumor cells through VP shunt. This case is a reaffirmation of the importance of brain tumor location and tissue diagnosis for the purpose of adjuvant treatment of neurosurgical lesions in the neurocritical care setting. It also highlights the role of catheters as potential routes of iatrogenic transmission not just in anterograde but also in a retrograde manner to the CNS, which is very unusual. This is the only second case to report retrograde flow of tumor cells from an extraneural source up the VP catheters. The authors suggest that intraperitoneal chemotherapy should be considered in the cases of known extraneural abdominal malignancies of high malignant potential with or without the presence of peritoneal infiltration in order to avoid dissemination through VP shunts.